Answer:
a=
![(c-by)/(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/moz3t9ua5ip8rpg40mbxeagof3isdociy6.png)
Explanation:
To find a, we need to change the equation so a is the variable that is left by itself. So...
ax+by=c Get rid of anything else besides the x and its coefficient.
-by -by
ax=c-by Because a has to be completely isolated, get rid of its coefficient.
/x /x
a=
![(c-by)/(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/moz3t9ua5ip8rpg40mbxeagof3isdociy6.png)
Hope this helps and have a great day :D